"Estudio retrospectivo de dermatosis producidas por ácaros y hongos en los pacientes caninos, atendidos en el Hospital Docente Veterinario "Dr.César Augusto Guerrero" de la Universidad Nacional de Loja, período 2012-2015 - Ruano Peña, Thalia Elizabeth (2018)
The purpose of this research has been a retrospective analysis of the dermatitis produced by mites and fungus in canine patients that arrived to the Hospital Docente Veterinario “Dr. César Augusto Guerrero” of the Universidad Nacional of Loja during the 2012-2015 period. This research was carried out with the information obtained from the records of the clinic histories in the hospital. The information was categorized and analyzed taking into account the following variables: age, race, sex, anatomic region, and presumed diagnosis. The study was carried out on 204 cases which were divided into different groups according to the dermatitis they presented, with the objective of obtaining the possible causes of such pathologies. With relation to the age, young patients were more affected. In relation to race, the most affected one was Poodle 11% (23 dogs), followed by Schnauzer 7% (14 dogs) as well as Bulldog, Pit Bull 6% (12 dogs), Peskiness 5% (10 dogs), and 50 cases were mestizo patients, that is, 25%. In relation to sex, male patients were mostly affected 58% (118 dogs). The anatomic region mostly injured was the cervical scalp 44% (90 dogs), followed by the caudal zone 31% (65 dogs), the generalized 13% (30 dogs), the thoracic one 7% (10 dogs), and the medium abdominal 5% (9 dogs). The most frequently diagnosed dermatitis was demodicosis which affected 76.9% (157 dogs), demodicosis plus malassezia 15% (31 dogs), demodicosis plus dermatophytosis 1.9% (4 dogs), and demodicosis plus sarcoptic scab, demodicosis plus mucormycosis, sarcoptic scab, and malassezia 0.9% each (2 dogs). Key Words: retrospective analysis, canines, dermatitis, demodicosis, sarcoptic scab, mites, fungus.